7. DISEASE MODEL AND SOME LABORATORY INDICATORS OF ATO CYCLE HEMODIALYSIS PATIENTS AT TRANSPORT HOSPITAL IN 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe disease patterns and analyze the association between dialysis duration, age, and hematological–biochemical indices in chronic hemodialysis patients.Methods: A cross-sectional study was conducted on 125 patients at Transport Hospital (2023–2024). Clinical, hematological, and biochemical data were compared between patients with 5 years of dialysis, and multivariate regression was performed with age and dialysis duration.Results: Hypertension surpassed glomerulonephritis as the leading cause of end-stage renal disease. Patients with shorter dialysis duration had more comorbidities (hypertension 68.3%, diabetes 23.8%). Longer dialysis duration correlated positively with reticulocyte ratio (Coef = 0.03; p
Keywords: chronic hemodialysis, disease pattern, hematological indices, biochemical indices.